Conceptualising an epistemology of praxis for teaching research in Information Systems - Uys, Walter Ferreira (Department of Information Systems, 2019)
This dissertation engages with the perennial question of ‘how lecturers learn to teach’ and ‘students learn to learn’, through engaging with the development of one lecturer in the process of learning how to teach undergraduate students to do research in Information Systems at a Higher Education Institution in South Africa. Teaching and learning stand at the core of Higher Education, yet at the University where this research was conducted, 86% of the academics in the Faculty have no formal qualification in teaching and only extended programme students are enrolled in academic literacy courses. Teaching and learning are also not typical competencies that are included in discipline-specific curricula. Because lecturers are appointed as educators, it becomes a moral imperative for them to become proficient in teaching and learning. This thesis takes the position that adult educators and learners are able to teach themselves under the right circumstances. The research was based on a case study of learning to teach three groups of third year students over a consecutive period of three years in a research methods and philosophy course in Information Systems at a historically disadvantaged University in SA. Political imperatives of free and open access to higher education and the associated growth in student numbers, together with constrained financial resources and increasing academic workloads provide the context for this research against the Universities strategy to transition from a teaching to a research-based institution. These imperatives require new and innovative ways of teaching large groups of underprivileged students with minimal resources for doing research. Furthermore, the widespread adoption of the internet by students as their primary source of information has exposed a critical need for these kinds of academic literacies in discipline specific curricula. It is suggested that these skills can only be developed through practical experience and not as a theoretical curriculum. Praxis is guided by the Greek concept of phronēsis; which is the moral disposition to do what is right depending on the circumstances. By analysing the course reflections of 60 students using Aristotle’s dialectics, this dissertation provides empirical evidence of ‘how students learn’, ‘how to teach’ students to be self-directed as well as ‘how’ academics are able to learn to teach themselves. It is suggested that the current practice of prescribing to students what, when, where and why they should learn is harmful to their long-term self-directing capabilities. By fostering students’ independence through enabling them how to learn, the lecturer reflexively becomes free to learn how to teach for him/herself. More importantly, this research has highlighted the absence of a knowledge component in contemporary models of experiential learning. These findings have implications for the broader sphere of teaching of research in Information Systems as well as developing students’ critical and self-directed faculties. This is of value in preparing students for postgraduate research in any discipline, for developing students as lifelong learners, and in developing lecturers as critically reflective educators who know ‘how’ and ‘why’ to teach.